Sosialisasi Peran Karang Taruna dalam Pengembangan Pariwisata di Pemandian Lubuk Mande Rubiah Kota Padang - Dea Salsabilla; Aulia Bunga Adri Elisa; Melisa Diah; Yulia Hanoselina (Lembaga Pengembangan Kinerja Dosen, 2025)
Community-based tourism is a form of tourism development managed by local communities with the aim of providing direct benefits to the local population. Lubuk Mande Rubiah Subdistrict in Padang City has promising natural tourism potential, yet youth involvement in its development remains limited. This study aims to examine the socialization of the role of Karang Taruna (youth organization) in supporting tourism development in the area. The research employed a descriptive qualitative approach through field observation and interviews with local youths involved in Karang Taruna. The results indicate that Karang Taruna contributes to managing ticketing, maintaining the cleanliness of the site, and initiating promotional efforts through social media. However, the lack of training and supporting facilities poses significant challenges to fully realizing this potential. The socialization efforts focused on strengthening youth capacity, increasing awareness of tourism promotion, and providing a sample digital product in the form of a promotional video. These findings imply that, with the right approach, Karang Taruna can serve as a driving force in building a sustainable tourism ecosystem rooted in local community participation. Keywords: , ,